GSLPI: A Cost-Based Query Progress Indicator - Li, Jiexing; Nehme, Rimma V.; Naughton, Jeffrey (International Conference on Data Engineering, 2012)
Progress indicators for SQL queries were first published in 2004 with the simultaneous and independent proposals from Chaudhuri et al. and Luo et al. In this paper, we implement both progress indicators in the same commercial RDBMS to investigate their performance. We summarize common cases in which they are both accurate and cases in which they fail to provide reliable estimates. Although there are differences in their performance, much more striking is the similarity in the errors they make due to a common simplifying uniform future speed assumption. While the developers of these progress indicators were aware that this assumption could cause errors, they neither explored how large the errors might be nor did they investigate the feasibility of removing the assumption. To rectify this we propose a new query progress indicator, similar to these early progress indicators but without the uniform speed assumption. Experiments show that on the TPC-H benchmark, on queries for which the original progress indicators have errors up to 30X the query running time, the new progress indicator is accurate to within 10 percent. We also discuss the sources of the errors that still remain and shed some light on what would need to be done to eliminate them.